Stereotactic body radiotherapy for lung tumors: Preliminary results from a single institution - Eisaku YODEN; Kei KONISHI; Nobuhiko KAMITANI; Ryoji TOKIYA; Junichi HIRATSUKA; Masao NAKATA; Mikio OKA; Naomi NAGASE; Koki KAKUBA; Tadashi TANI; Makiko HIGUCHI (KAWASAKI MEDICAL JOURNAL (Japanese), 2012)
[ABSTRACT] Stereotactic body radiotherapy (SBRT) for small lung tumors has been reported to achieve very promising treatment outcomes. At our institution, 25 lesions in 22 patients were treated with this technique over a 5-year period. All patients had medically inoperable lung tumors <5 cm in size or had refused surgery. In cases of metastatic tumors, the number of lesions did not exceed 2. Radiotherapy was performed under strict patient immobilization with an exclusive fixation device. Tumor volumes were determined by 4-dimensional computed tomography, under free breathing, and the position of the radiation field was verified by linac graphy at each treatment. A total of 48 Gy in 4 fractions was delivered by 6-10 non-opposed beams. The 3-year local control rate was 92% for primary lung cancer and 75% for metastatic lung cancer. The 3-year overall survival rate for primary and metastatic lung cancers were 65% and 56%, respectively. Metastasis from colorectal cancer was associated with poor local control. Severe adverse effects were not observed. The SBRT method used provided safe and effective treatment.